Progression of foveola-on rhegmatogenous retinal detachment. Issue 11 (24th June 2014) - Hajari, Javad Nouri; Kyhnel, Alexander; Bech-Azeddine, Julia; la Cour, Morten; Kiilgaard, Jens Folke
Abstract : Aims: Quantitative assessment of the rate of progression of recent onset posterior rhegmatogenous retinal detachment (RRD). Methods: A prospective observational study on patients presenting with acute symptomatic primary foveola-on RRD over a 32-month period. Patients were evaluated with optical coherence tomography (OCT) to confirm foveola status. A total of 96 eyes were enrolled and 50 were eligible for quantitative measurement of the movement of the detachment by OCT. Results: Only one eye progressed from foveola-on to foveola-off in the 96 evaluated eyes. In seven of the 50 eyes eligible for quantitative measurement, the detachment was stable during admission. In all others, the movement was very dynamic with episodes of progression and regression. We found that 18% (9/50) of the detachments had a net movement towards foveola during admission. Logistic regression established the amount of time admitted (OR=1.05, p=0.027) as significant risk factor for progression. Conclusions: The risk of progression of a foveola-on RRD to affect the fovea is small the first night of admission (1%). The amount of time surgery is delayed was found as significant risk factor for progression towards foveola.